Digitalisation of the European Small Claims Procedure through Blockchain - Giacalone, Marco; Arnone, Gioia (Revista Ítalo-española de Derecho procesal, 2025)
The study explores blockchain's potential in transforming the European Small Claims Procedure (ESCP), proposing its integration into the ESCP paradigm for cross-border disputes under €5,000. It reviews the legal digitalisation and blockchain literature, noting its gradual adoption in public administration. Using a mixed-method approach, quantitative analysis found no significant impact on ESCP turnaround times or stakeholder satisfaction, while qualitative data highlighted benefits in transparency and effectiveness. However, challenges in technical integration, scalability, and legal frameworks remain. The paper concludes cautiously optimistic, emphasising ongoing research and collaboration between IT and legal professionals.